1988
DOI: 10.2118/15668-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spreading and Nonspreading Oils on Foam Propagation Through Porous Media

Abstract: Experiments show that a spreading oil increases the time for foam generation and decreases the speed of foam propagation in a porous medium. It also breaks a foam faster than a nonspreading oil. These findings may be important in interpreting results of different foam displacement experiments and therefore surfactant selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…It is widely accepted that these interactions are governed by three main mechanisms; entry of oil droplet into gas-liquid interface [32,33], spreading of oil on the gas-liquid interface [34], and formation of an unstable bridge across lamella [35]. As discussed in Schramm and Novosad [24] the thermodynamic feasibility of oil destroying foam can be determined by evaluating the entering coefficient (E), spreading coefficient (S) and bridging coefficient (B).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that these interactions are governed by three main mechanisms; entry of oil droplet into gas-liquid interface [32,33], spreading of oil on the gas-liquid interface [34], and formation of an unstable bridge across lamella [35]. As discussed in Schramm and Novosad [24] the thermodynamic feasibility of oil destroying foam can be determined by evaluating the entering coefficient (E), spreading coefficient (S) and bridging coefficient (B).…”
Section: Introductionmentioning
confidence: 99%
“…To destabilize a foam lamella, an oil drop must first overcome electrostatic or steric interactions in the aqueous pseudoemulsion film, which forms as the drop approaches the gas/water interface (Nikolov et al 1986;Manlowe and Radke 1990). Then, provided that the aqueous phase does not spread at the gas/oil interface so formed, the oil forms a lens that can destabilize the lamella by spreading along the gas/water interface (Lau and O'Brien 1988), by bridging (Garrett 1992), or by some combination of the two. It is a common observation during phase behavior of oil/water/surfactant systems that foam is more stable with Winsor I phase behavior and more unstable with Winsor II or III phase behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In general, an increase in salinity tends to decrease the CMC and to increase the surface viscosity of the surfactant solution. High salinity increases the adsorption capacity of kaolinite [55] and sands [76,77]. However, some surfactants perform best in the absence of electrolytes [74].…”
Section: Foam In Porous Mediamentioning
confidence: 99%
“…Result, s of Lau _md O'I3rien [76] show tl_at; flu' presence of a spre_cling oil slows down foam generation and decreases foam propagation rat;e, Mmllowe and l:{,a,dl<e [81] indicated that foam sta,bility in porous media is'dependent ttpoll l,he stability of pseudoemulsiozl films (liquid films between oil and g_s). Collapse of these films c_tzses foam lamellae to rup_,urc,,…”
Section: Presence Of Oilmentioning
confidence: 99%